Investigation for the Interaction of Tyramine‐Based Anthraquinone Analogue with Human Serum Albumin by Optical Spectroscopic Technique. (26th December 2012) - Aggarwal, Swati; Tiwari, Anjani K.; Srivastava, Pooja; Chadha, Nidhi; Kumar, Vikas; Singh, Gurmeet; Mishra, Anil K.
<x xml:space="preserve">Abstract</x> A newly synthesized anthraquinone derivative 'N‐(2‐methylanthraquinone)‐4‐(2‐aminoethyl) phenol' (Tyan) were characterized as a fluorophore from photophysical analysis by measuring the UV‐Vis absorptive (λex = 325 nm) and fluorescence emitive (λem = 660 nm) values. Density functional theory additionally supported the spectroscopic data by modulation of highest occupied molecular orbital rather than lowest unoccupied molecular orbital due to the affect of tyramine moiety present in Tyan. The pharmacological importance of Tyan was evaluated by molecular docking with human serum albumin. The molecular docking of the Tyan was performed with the crystal structure of human serum albumin (PDB entry 1E78), which shows binding in all the three domains of human serum albumin corresponding to −7.74 as the GScore. Moreover, the interactions of human serum albumin with Tyan were assessed employing fluorescence spectroscopy under simulative physiological conditions, and the binding constant for the interaction at 25 °C was found to be 0.6 × 103/m.